2012
DOI: 10.3409/fb60_3-4.181-187
|View full text |Cite
|
Sign up to set email alerts
|

Carcass, Meat Quality and Histochemical Traits of m. longissimus lumborum from Złotnicka Spotted Pigs and Commercial Pigs

Abstract: Carcass, meat quality and muscle fibre traits of m. longissimus lumborum were studied in 61 Z³otnicka Spotted (ZS) pigs and 35 commercial crossbred (Polish Large White × Polish Landrace) pigs. The animals received organic feed ad libitum and were slaughtered at 210 days of age. The current findings indicate that both slaughter weight and cold carcass weight were significantly lower, and backfat thickness higher for ZS pigs compared to commercial pigs, while the commercial pigs exhibited longer carcasses and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Polish indigenous breeds achieved middle values, but crossbreed Ma × Du had higher back-fat thickness (P < 0.001). These results are in agreement with findings reported by Grzeškowiak et al (2009), Jankowiak et al (2009 and Bocian et al (2012). Wojtyšiak and Poltowicz (2014) showed that Pulawska had lower value of loin eye area, but higher back-fat thickness than their crossbreeds.…”
Section: Resultssupporting
confidence: 93%
“…Polish indigenous breeds achieved middle values, but crossbreed Ma × Du had higher back-fat thickness (P < 0.001). These results are in agreement with findings reported by Grzeškowiak et al (2009), Jankowiak et al (2009 and Bocian et al (2012). Wojtyšiak and Poltowicz (2014) showed that Pulawska had lower value of loin eye area, but higher back-fat thickness than their crossbreeds.…”
Section: Resultssupporting
confidence: 93%
“…The present results are typical of local breeds and meat-type breeds (RUUSUNEN & PUOLANNE 1997;SERRA et al 1998;BOGUCKA & KAPELAÑSKI 2005;RYU et al 2008;WOJTYSIAK 2014). The effect of breed on muscle microstructure has also been confirmed by BOCIAN et al (2012), who reported that m. longissimus lumborum in Z³otnicka Spotted pigs has a significantly higher proportion of type I fibres and a lower proportion of type IIB fibres compared to the commercial crossbreeds. According to K£OSOWSKA and FIELDIER (2003), the proportion of individual muscle fibre types has a genetic background and is characteristic of different breeds and crossbreds.…”
Section: Resultssupporting
confidence: 86%
“…The effect of breed on drip loss value was observed by many authors. BOCIAN et al (2012) found that the meat from Z³otnicka Spotted pigs had lower drip loss compared to the meat of commercial crossbreeds. Similarly, JANKOWIAK et al (2009) noted lower drip loss in the meat of purebred pigs compared to the crossbreeds.…”
Section: Resultsmentioning
confidence: 95%
“…In many countries native pig breeds can provide suitable material for the good-quality products from pork that are more frequently demanded by consumers at present ( Serrano et al, 2008 ). One possible way to improve pork quality is to put greater emphasis on native breeds of pigs ( Bocian et al, 2012 ). Ruusunen et al (2012) stated that the biggest differences in carcass and meat quality traits are usually found when comparing pigs of two genetically different pig breeds, i.e.…”
Section: Introductionmentioning
confidence: 99%